THE RELATIONSHIP BETWEEN SELF-ESTEEM LEVEL AND QUALITY OF LIFE OF PATIENTS CHRONIC RENAL FAILURE PATIENTS UNDERGOING HEMODIALYSIS: A STUDY LITERATURE REVIEW - Khamid , Abdul; Fadia, Silmi; Virgita, Nanda; Rindayani, Ririn; Putri, Meilisa Septiyani; Suntia , Putri Della; Azizah, Siti Nur; Victoria, Safinatunnajah; Nur, Marrotin; Umam, Khoirul; Nanda, Nanda; Putra, Riyan Arya (HEARTY, 2026)
Chronic renal failure (CKD) is a global health issue. Patients with renal failure will generally undergo renal replacement therapy which may affect their quality of life. Several studies have shown that patients with chronic renal failure who undergo dialysis will experience a decrease in quality of life. Therefore, it is important to study the factors associated with self-esteem and quality of life of chronic renal failure patients undergoing hemodialysis. The aim is to determine the relationship between self-esteem and quality of life with chronic renal failure patients undergoing hemodialysis. The research method used was a search of several databases, namely PubMed, Google Scholar and Science Direct and a review of several studies that fit the inclusion and exclusion criteria. The result is that there is a significant relationship between self-esteem and the quality of life of chronic renal failure patients undergoing hemodialysis. Based on the analysis of the eight research articles reviewed, it can be concluded that there is a significant relationship between self-esteem and the quality of life of chronic renal failure patients undergoing hemodialysis.